Young people's use of NHS Direct: a national study of symptoms and outcome of calls for children aged 0–15. Issue 12 (9th December 2013) - Cook, E J; Randhawa, G; Large, S; Guppy, A; Chater, A M; Pang, D
Abstract : Objectives: National Health Service (NHS) Direct provides 24/7 expert telephone-based healthcare information and advice to the public in England. However, limited research has explored the reasons to why calls are made on behalf of young people, as such this study aimed to examine call rate (CR) patterns in younger people to enable a better understanding of the needs of this population in England. Setting: NHS Direct, England, UK. Participants and methods: CRs (expressed as calls/100 persons/annum) were calculated for all calls (N=358 503) made to NHS Direct by, or on behalf of, children aged 0–15 during the combined four '1-month' periods within a year (July 2010, October 2010, January 2011 and April 2011). χ² Analysis was used to determine the differences between symptom, outcome and date/time of call. Results: For infants aged <1, highest CRs were found for 'crying' for male (n=14, 440, CR=13.61) and female (n=13 654, CR=13.46) babies, which is used as a universal assessment applied to all babies. High CRs were also found for symptoms relating to 'skin/hair/nails' and 'colds/flu/sickness' for all age groups, whereby NHS Direct was able to support patients to self-manage and provide health information for these symptoms for 59.7% and 51.4% of all cases, respectively. Variations in CRs were found for time and age, with highest peaks found for children aged 4–15 in the 15:00–23:00 period and in children aged <1 in the 7:00–15:00 period. Conclusions: This is the first study to examine the symptoms and outcome of calls made to NHS Direct for and on behalf of young children. The findings revealed how NHS Direct has supported a range of symptoms through the provision of health information and self-care support which provides important information about service planning and support for similar telephone-based services.